2014
DOI: 10.1185/03007995.2014.909393
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hydroxychloroquine in the treatment of type 2 diabetes mellitus: a double blind, randomized comparison with pioglitazone

Abstract: The sample size for this study was small. However, based on the encouraging results of this proof-of-concept study, longer duration studies in larger population can be conducted to further confirm these findings. TRIAL REGISTRATION DETAILS: Clinical Trial Registry-India URL: http://ctri.nic.in, Registration Number: CTRI/2009/091/001036.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 24 publications
3
74
0
Order By: Relevance
“…There was a significant reduction in the mean HbA1c, FBG and PPG from baseline at week 24 in both the groups. 8 A marginal weight reduction of 1.08 kg was also reported with hydroxychloroquine in that study. All the trials till now conducted with Hydroxychloroquine 400mg has confirmed its superior potency of HbA1c reduction in uncontrolled T2DM patients.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…There was a significant reduction in the mean HbA1c, FBG and PPG from baseline at week 24 in both the groups. 8 A marginal weight reduction of 1.08 kg was also reported with hydroxychloroquine in that study. All the trials till now conducted with Hydroxychloroquine 400mg has confirmed its superior potency of HbA1c reduction in uncontrolled T2DM patients.…”
supporting
confidence: 53%
“…A double-blinded, randomized study of 267 patients with uncontrolled T2DM was conducted by Pareek et al 8 That study conclusively showed that hydroxychloroquine had a similar anti-hyperglycaemic effect as pioglitazone among the patients refractory to metformin and sulfonylurea treatment. Based on this study, hydroxychloroquine 400mg has been officially approved by drug regulatory authority of India to improve glycemic control of T2DM patients on metformin, sulfonylurea combination as an adjunct to diet and exercise therapy.…”
mentioning
confidence: 99%
“…A double-blinded, randomized study of 267 patients with uncontrolled T2DM was conducted by Pareek et al [10] in 2014 in India. This study conclusively showed that hydroxychloroquine had a similar anti-hyperglycaemic effect as pioglitazone among the patients refractory to metformin and sulfonylurea treatment.…”
Section: Discussionmentioning
confidence: 99%
“…22 ( Table 1). Another RCT by Gerstein et al on 135 patients with T2DM resistant to sulfonylureas showed significant reduction of HbA1c (-0.96%) with 18 months of HCQ without significant improvement in insulin resistance.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Mechanisms responsible for altered lipid profiles with chloroquine analogue treatment include a significant increase in lipid clearance rate and up-regulation of LDL receptors. 6,8,10,11,20,22 In this context chloroquine is effective as both hypolipidaemic and antidiabetic drug.…”
mentioning
confidence: 99%